Marketing Strategy for Strengthening Competitiveness of Small and Medium Enterprises (SMEs) Instant Sambel Post-Covid-19 Pandemic (Case Study of CV Progressive Gresik) - Narto (School of Industrial and System Engineering, Telkom University, 2021)
The Covid-19 pandemic that occurred in all countries in the world caused policy shifts globally. Therestriction of public activities in general in all sectors greatly affects the productivity of business actors,especially Small and Medium Enterprises (SMEs) CV Progressive Mengare Gresik instant sauce. Thedecline in product sales is the result of changes in consumer demand behavior. The post-Covid-19pandemic marketing strategy is needed to increase business competitiveness. SWOT analysis integratesinternal and external factors by developing alternative strategies using the SWOT and QSPM matrices todetermine the priority of marketing strategies to improve business competitiveness after the Covid-19pandemic. The research objective is to make efforts to formulate a marketing strategy after the Covid-19pandemic to strengthen the level of business competitiveness of CV Progressive Mengare Gresik SambelInstant SMEs. The results of the strategy formulation are expected to help SMEs in improving themarketing network and sales of the Mengare Gresik instant chili sauce product. The results showed that theposition of instant sambel SMEs CV Progressive Mengare Gresik was in quadrant V with IFAS value2.7037 and EFAS value 2.9416. Alternative strategies based on the priority value of the QSPM matrix of4.9621, namely increasing product promotion through digital marketing and digital branding to expand themarketing network through the marketplace and collaboration with related agencies and local governments